STUDY ANALYSIS OF BUKIT ASAM TALENT MANAGEMENT (BATMAN) IN CAREER DEVELOPMENT AND PROMOTION OF EMPLOYEE POSITIONS AT PT BUKIT ASAM TBK - Hendri Dunan; Maria Angeline (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study focuses on the issue of insufficient career development options that align with the interests and abilities of individual employees, which hinders the improvement of organizational capacities. The challenges faced include uncertainty, lack of transparency, and limited employee history data, all of which pose significant obstacles to employee promotion and career progression. To address these challenges, the research aims to thoroughly explore and explain the application of talent management in the career development and advancement processes at PT Bukit Asam Tbk. One of the main objectives is to uncover how talent management strategies can effectively navigate the complexities brought about by uncertainties and limited transparency. Additionally, the study aims to shed light on the innovative approach of integrating the Bukit Asam Talent Management (BATMAN) system, a framework based on talent management principles, into the organizational structure. BATMAN is expected to act as a catalyst in overcoming the obstacles associated with career development and progression. Using a descriptive qualitative study design, the researcher systematically examines the intricate dynamics between PT Bukit Asam Tbk's Integrated Talent Management System (ITMS) framework and the BATMAN process. Through the analysis of data extracted from the BATMAN system, employee interviews, observation activities, and consultation with other relevant sources, the study seeks to provide a comprehensive understanding of the mutually beneficial relationship between talent management principles and the organizational context at PT Bukit Asam Tbk.